A study to assess the Aedes mosquto diversity and the different mosquito genera in a rural area in Thrissur, Kerala - Wilson, Anitha; Krishnadas, V. T.; Saju, C. R.; Rafi, M. Mohammed (International Journal Of Community Medicine And Public Health, 2022)
Background: Mosquito is one of the leading causes of vector borne causing infections leading to morbidity and mortality worldwide. It is the reason for spreading various viral, parasitic infections to humans. India has favorable climatic and environment conditions for mosquito breeding and in addition to these, influence of human activity has been significant in the increased breeding of mosquitoes. The objective of the study was to determine the various artificial containers which led to the Aedes mosquito larvae breeding and to understand the various mosquito genera in a rural area in Kerala. Methods: A cross sectional study was conducted over a period of 4 months September, October, December and January in a ward of Kaiparambu Panchayath, Thrissur. A house-to-house survey was done where every water holding containers outdoor and indoor of each house was inspected, looked for larvae, collected and examined. Adult mosquitoes were also collected from the premises. Results: Total house examined were 520 over four months and positive containers were 271. The House index, Container index and Breteau index for the 4 months were moderate to high risk level. Maximum breeding was seen in plastic containers and the most common species identified during larval and adult stages from indoor and outdoor were Aedes albopictus. Conclusions: Mosquitoes are the main risk for various vector borne diseases. Influence of manmade habitats has been significant in the increase of mosquito diversity. By educating the people, appropriate waste management and reducing use of plastics can to extent reduce the problems associated.